PENYULUHAN PERILAKU HIDUP BERSIH DAN SEHAT MENINGKATKAN PENGETAHUAN SISWA SMA MERAH PUTIH DI DOKULAMO KECAMATAN GALELA BARAT - Cabu, Roberto; Christin Fika, Elfira (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2021)
The outreach activities that have been carried out at Red and White Dokulamo High School, West Galela District, North Halmahera Regency, aim to improve the quality of public health through the process of building awareness so that it can help prevent the spread of COVID-19 in the school environment, especially for students and teachers. The method used is counseling and question and answer. The results of the activity show that students and teachers at SMU Merah Putih Dokulamo already have knowledge related with healthy living behavior which includes the habit of washing hands, using school latrines, eradicating mosquito larvae regularly, disposing of garbage regularly and participating in sports activities.